2015
DOI: 10.1093/nar/gkv115
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput data integration of RNA–miRNA–circRNA reveals novel insights into mechanisms of benzo[a]pyrene-induced carcinogenicity

Abstract: The chain of events leading from a toxic compound exposure to carcinogenicity is still barely understood. With the emergence of high-throughput sequencing, it is now possible to discover many different biological components simultaneously. Using two different RNA libraries, we sequenced the complete transcriptome of human HepG2 liver cells exposed to benzo[a]pyrene, a potent human carcinogen, across six time points. Data were integrated in order to reveal novel complex chemical–gene interactions. Notably, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 45 publications
1
87
0
1
Order By: Relevance
“…miR-29b-3p was also identified among B a P-mediated alterations and subsequent miRNA-mRNA interactions in mouse primary hepatocytes (miR-29b-3p and Col4a2 , miR-24-3p and Flna ), which were also found to be involved in cell cycle arrest and the impairment of repair mechanisms of DNA damage [71]. miR-181a-1-3p, was overexpressed in HEPG cells treated with B a P, and one of its targets, MGMT , a gene that encodes an enzyme involved in DNA damage repair, was decreased at the mRNA level [72]. In a study of human liver HepRG cells, treatment with B a P caused over-expression of miR-410 [73].…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 99%
“…miR-29b-3p was also identified among B a P-mediated alterations and subsequent miRNA-mRNA interactions in mouse primary hepatocytes (miR-29b-3p and Col4a2 , miR-24-3p and Flna ), which were also found to be involved in cell cycle arrest and the impairment of repair mechanisms of DNA damage [71]. miR-181a-1-3p, was overexpressed in HEPG cells treated with B a P, and one of its targets, MGMT , a gene that encodes an enzyme involved in DNA damage repair, was decreased at the mRNA level [72]. In a study of human liver HepRG cells, treatment with B a P caused over-expression of miR-410 [73].…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 99%
“…CircRNAs can act as miRNA sponges [8,10] and can function in gene regulation as transcription regulators interacting with the Pol II transcription complex [11] or by competing with linear splicing [12]. Other investigators have reported that circRNAs are involved in the growth of colorectal and ovarian cancers [13], and be associated with DNA damage in breast cancer cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that circRNAs participate in many essential biological processes and play important role as miRNA sponge [19-23]. However, there is no studies to date have reported the effects of circRNAs in patients with repeated implantation failure.…”
Section: Discussionmentioning
confidence: 99%